Comparing anastomosis techniques on ischemia time in multi-arterial kidney grafts: a systematic review and meta-analysis - Hernawan Rahmat Muharia, Bayu; Situmorang, Gerhard Reinaldi; Rasyid, Nur; Rodjani, Arry; Birowo, Ponco (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Kidney transplants with multiple renal arteries (MRAs) address donor shortages but carry higher vascular risks than single renal arteries. This study aimed to evaluate how different anastomosis techniques affect outcomes in kidney transplants with MRAs through meta-analysis and systematic review, concluding the continuous discussion about the best reconstructive strategy. METHODS A comprehensive search across 5 databases (PubMed, ScienceDirect, Cochrane Library, Web of Science, and the Cumulative Index to Nursing and Allied Health Literature) was conducted until December 17, 2024, to find studies comparing anastomoses technique in MRA grafts. Meta-analysis was performed using Review Manager software version 5.4, generating pooled effect estimates for mean difference (MD) and risk ratio (RR), two-sided p-values, and 95% confidence intervals (CIs). RESULTS Two retrospective cohort studies were included in the meta-analysis. There was no significant difference between end-to-side and side-to-side anastomosis in warm ischemia time (MD = 15.64, 95% CI: −6.82−38.10, p = 0.17) or cold ischemia time (MD = −16.74, 95% CI: −105.61−72.14, p = 0.71). The complication rate showed no significant variation between side-to-side and end-to-side anastomosis (RR = 2.38, 95% CI: 0.41−13.70, p = 0.33). Meta-analysis on graft function and rejection was impossible due to differences in measurements and the small number of studies. CONCLUSIONS Different anastomosis techniques for MRA grafts did not result in longer ischemia times or higher complication rates. Graft function and rejection rates were comparable between side-to-side and end-to-side anastomosis, suggesting both were equally feasible for renal transplants with MRAs. Further studies are required to verify these findings.